Antioxidant and Antibacterial Activity of Pomegranate Extract (Punica granatum L.) in Lip Balm Formulation - Maria Grasela Kase; Aniek Prasetyaningsih; Dwi Aditiyarini (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2023)
Lips are a part of the face that does not have hair follicles making them easily dry and crack. Lipbalm is a beauty product that could be used to solve this problem by increasing lip moisture. However, the synthetic ingredient in commercial lip balm can have side effects on the body in the long term. Pomegranate fruit is one of the natural ingredients containing anthocyanin which can be used as a natural dye, antioxidant, and antibacterial. Therefore, this study was performed to study the potency of pomegranates as natural dyes, antioxidants, and antibacterial in lip balm. Pure pomegranate juice was obtained through squeeze step. Lip balm was prepared in several concentrations of pomegranate juice which were 0%, 12.5%, 18.75%, and 25%. Phytochemical screening shows the content of anthocyanin, saponin, tannin, and flavonoid. In this study, pomegranate juice has low antioxidant activity with IC50 449 ppm. Lip balm formula with 18.75% and 25% of pomegranate juice can inhibit the growth of the bacteria Staphylococcus aureus.